Follow-up over Indigenous Lands in Pernambuco, Brazil: diagnosis of right to property of indigenous people - Barbosa da Cunha, Luis Emmanuel; Amorim, Jerfferson (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
This paper presents partial results of the monitoring project on the demarcation of indigenous lands in the State of Pernambuco, Brazil. The project provides for the monitoring of demarcation processes for 15 (fifteen) years, in three stages. The first stage is diagnosis. The methodology consists of identifying procedural acts through legal analysis, identifying indigenous peoples who claim ownership (right to property) of their ancestral lands and the current state of demarcation processes through information accessed through FUNAI and civil society. With this, it is possible to make an evaluation of the realization of the right to communal property and prepare the other two stages of the research in order to understand how fundamental rights of indigenous people are made effective.